A research agenda for sustainability and business - Russell, Sally V.; Padfield, Rory W. (Elgar research agendas, 2023)
"How businesses can and are acting to redress social and environmental issues is a question of growing academic interest. Bringing together a range of interdisciplinary perspectives, this insightful Research Agenda evaluates the current state of the art of sustainability and business and assesses key challenges for the field. Multidisciplinary chapters provide instrumental, economic, network and political perspectives on issues that are crucial in gaining insight into sustainability challenges facing businesses today, from socially responsible consumption behaviours and organisational resilience to climate change and sustainability transitions in extractive industries. Its diverse contributions highlight the breadth and depth of analyses and perspectives that are necessary to set a dynamic agenda for future research on sustainability and business. Advancing novel research questions and methodologies, the editors illustrate the path ahead for carrying out research that impacts the science and practice of business and sustainability, as well as creating meaningful change for our species and planet. Offering an advanced yet accessible introduction to the current state and future direction of sustainability and business, this incisive Research Agenda will be an invaluable resource for students and scholars of business, sustainability studies, and environment studies. Its practical insights will also benefit MBA students and business executives moving into sustainability"--